2021
DOI: 10.1037/xge0000956
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal transcranial direct current stimulation (tDCS) has a domain-specific impact on bilingual language control.

Abstract: Researchers debate whether domain-general cognitive control supports bilingual language control through brain regions such as the dorsolateral prefrontal cortex (DLPFC). Transcranial direct current stimulation (tDCS) is a method to alter brain activity, which can lead to causal attribution of task performance to regional brain activity. The current study examined whether the DLPFC enables domain-general control for between-language switching and nonlinguistic switching and whether the control enabled by DLPFC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Hence, the interplay of inhibition and activation figures much more prominently in the nonlinguistic control literature than in the language control literature. While we recognize that some prior studies have shown that there is no one-to-one mapping between bilingual language control and nonlinguistic control (e.g., Calabria et al, 2012, 2015; Jylkkä, Lehtonen, Lindholm, et al, 2018; Stasenko et al, 2017; Vaughn et al, 2021), we believe that the analogy of these two domains could be developed further at the theoretical level (see Graham & Lavric, 2021, for a recent discussion). For bilingualism research, this would imply that inhibitory control is only one of several control processes.…”
Section: Requirements Of a Bilingual Inhibitory Control Markermentioning
confidence: 90%
See 1 more Smart Citation
“…Hence, the interplay of inhibition and activation figures much more prominently in the nonlinguistic control literature than in the language control literature. While we recognize that some prior studies have shown that there is no one-to-one mapping between bilingual language control and nonlinguistic control (e.g., Calabria et al, 2012, 2015; Jylkkä, Lehtonen, Lindholm, et al, 2018; Stasenko et al, 2017; Vaughn et al, 2021), we believe that the analogy of these two domains could be developed further at the theoretical level (see Graham & Lavric, 2021, for a recent discussion). For bilingualism research, this would imply that inhibitory control is only one of several control processes.…”
Section: Requirements Of a Bilingual Inhibitory Control Markermentioning
confidence: 90%
“…Furthermore, studies comparing language switching and task switching indicate that there is no straightforward mapping of the processes involved in these two paradigms (e.g., Calabria et al, 2012, 2015; Declerck et al, 2017, 2021a; Jylkkä, Lehtonen, Lindholm, et al, 2018; Stasenko et al, 2017; Vaughn et al, 2021; see also Bialystok et al, 2004; Paap et al, 2017; Paap & Greenberg, 2013). For instance, Declerck et al (2017) found no switch cost difference when directly comparing language switching and task switching, whereas Calabria et al (2015) found no age effect on task switch costs but a decrease of language switch costs with increasing age.…”
Section: Inhibitory Phenomena In Bilingual Language Productionmentioning
confidence: 99%
“…As we move toward harnessing the insights for application/intervention from the basic science research looking into potential connections between bilingualism and cognitive aging, research that employs other methods, such as Trancranial direct current stimulation (tDCS) and/or Transcranial magnetic Stimulation (TMS), are also welcome. While these methods have both basic science application and therapeutic potential, especially as paired with cognitive training for the functional connectivity of working memory in the elderly (Nissim et al, 2019;Indahlastari et al, 2021), and although they have been used in bilingual language control research showing some promising effects in studies focusing on younger bilinguals (Hämäläinen et al, 2018;Radman et al, 2018;Jost et al, 2020;Tong et al, 2020;Zhu and Sowman, 2020;Vaughn et al, 2021), these methods are virtually unknown in the literature on bilingualism and cognitive aging.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to imaging techniques and invasive clinical language mapping methods (e.g., electrocorticography), we have gained further understanding of how various LMs modulate the neural organization of L1 and L2. The literature has demonstrated that bilingualism is associated with intricate structural and functional adaptations in the brain that also affect cognitive performance ( Vaughn et al, 2020 ; Cargnelutti et al, 2019 ; Fernández-Coello et al, 2017 ; Abutalebi et al, 2013 ; Abutalebi and Green, 2008 ). The adaptations occur in response to a wide range of experience-based factors.…”
Section: Discussionmentioning
confidence: 99%